Construction of Competitive Endogenous RNA Network and Verification of 3-Key LncRNA Signature Associated With Distant Metastasis and Poor Prognosis in Patients With Clear Cell Renal Cell Carcinoma - Su, Yang; Zhang, Tianxiang; Tang, Jieqiong; Zhang, Li; Fan, Song; Zhou, Jun; Liang, Chaozhao (Frontiers in Oncology, 2021)
Clear cell renal cell carcinoma (ccRCC) is a common malignancy with high distant metastasis rate. Long non-coding RNAs (LncRNAs) are reported to be up- or down-regulated in multiple cancers and play a crucial role in tumors metastasis or prognosis. Therefore, the purpose of our study is to construct a prognostic signature for ccRCC based on distant metastasis-related lncRNAs and explore the involved potential competitive endogenous RNA (ceRNA) network. The differentially expressed genes (DEGs) screened from The Cancer Genome Atlas (TCGA) database were used to construct a co-expression network and identify the distant metastasis-related module by weighted co-expression network analysis (WGCNA). Key genes with metastatic and prognostic significance were identified through rigorous screening, including survival analysis, correlation analysis, expression analyses in stage, grade, distant metastasis, and were verified in Gene Expression Omnibus (GEO) dataset and Gene Expression Profiling Interactive Analysis (GEPIA) database. The potential upstream miRNAs and lncRNAs were predicted via 5 online database and LncBase. Here, we constructed a ceRNA network of key genes which are significantly associated with the distant metastasis and prognosis of ccRCC patients. The distant metastasis-related lncRNAs were used to construct a risk score model through the univariate, least absolute shrinkage selection operator (LASSO), and multivariate Cox regression analyses, and the patients were divided into high- and low-risk groups according to the median of risk score. The Kaplan-Meier survival analysis demonstrated that the mortality was significantly higher in the high-risk group than in the low-risk group. Considering the other clinical phenotype, the Cox regression analyses indicated that the lncRNAs model could function as an independent prognostic factor. Real-time Polymerase Chain Reaction (RT-PCR) in ccRCC tissues and cells verified the high-expression level of 3 lncRNAs. Gene set enrichment analysis (GSEA) revealed that the lncRNA prognostic signature was mainly enriched in autophagy- and immune-related pathways, indicating autophagy and immune may play an important role in ccRCC distant metastasis. In summary, the constructed distant-metastasis related lncRNA signature could independently predict ccRCC patients prognosis, and the related ceRNA network provided a new sight on the potential mechanism of distant metastasis and promising therapy target for ccRCC.